Implikasi Mutasi dan Rotasi Kerja Terhadap Kinerja Dan Kepuasan ASN Di Lingkungan Sekretariat MPR RI - Moh Fajar Siddiq; Kusdiyana Kusdiyana; Theguh Saumantri; Gumilar Irfanullah (PEPAKEM: JURNAL HUKUM TATA NEGARA DAN POLITIK ISLAM, 2025)
Job transfers and rotations are instruments of civil service management used to meet organizational needs, develop competencies, and sustain performance. However, such policies may generate dissatisfaction when they are perceived as punishment, mismatch employees’ competencies, or are implemented without transparent procedures. This study analyzes the implementation of job transfers and rotations and their implications for civil servants’ performance and job satisfaction at the Secretariat General of the People’s Consultative Assembly of the Republic of Indonesia. It employs a qualitative empirical case-study approach. Data were collected through observation, interviews with officials and staff in the human resources unit, and analysis of personnel documents and relevant regulations. The data were examined through condensation, presentation, and conclusion drawing using the merit system, work design, and organizational justice as analytical frameworks. The findings show that transfers and rotations are used to align competencies with positions, fill organizational needs, broaden work experience, and reduce monotony. These policies can improve adaptability, cross-unit knowledge, and performance, but may reduce job satisfaction when the reasons for reassignment, selection criteria, and transition support are not adequately communicated. Their effectiveness therefore depends on competency fit, procedural transparency, employee readiness, and post-placement evaluation. This study proposes a four-stage implementation framework consisting of merit-based planning, transparent decisions, transition support, and outcome evaluation.